The Sodium Channel β4 Auxiliary Subunit Selectively Controls Long-Term Depression in Core Nucleus Accumbens Medium Spiny Neurons - Ji, Xincai; Saha, Sucharita; Gao, Guangping; Lasek, Amy W.; Homanics, Gregg E.; Guildford, Melissa; Tapper, Andrew R.; Martin, Gilles E. (Frontiers in Cellular Neuroscience, 2017)
Voltage-gated sodium channels are essential for generating the initial rapid depolarization of neuronal membrane potential during action potentials that enable cell-to-cell communication, the propagation of signals throughout the brain, and the induction of synaptic plasticity. Although all brain neurons express one or several variants coding for the core pore-forming sodium channel α subunit, the expression of the β (β1 to β4) auxiliary subunits varies greatly. Of particular interest is the β4 subunit, encoded by the Scn4b gene, that is highly expressed in dorsal and ventral (i.e. nucleus accumbens - NAc) striata compared to other brain regions, and that endows sodium channels with unique gating properties. However, its role on neuronal activity, synaptic plasticity, and behaviors related to drugs of abuse remains poorly understood. Combining whole-cell patch-clamp recordings with two-photon calcium imaging in Scn4b knockout (KO) and knockdown (KD) mice, we found that Scn4b altered the properties of action potentials (APs) in core accumbens medium spiny neurons (MSNs). These alterations are associated with a reduction of the probability of MSNs to evoke spike-timing-dependent long-term depression (tLTD) and a reduced ability of backpropagating action potentials to evoke dendritic calcium transients. In contrast, long-term potentiation (tLTP) remained unaffected. Interestingly, we also showed that amphetamine-induced locomotor activity was significantly reduced in male Scn4b KO mice compared to wild-type controls. Taken together, these data indicate that the Scn4b subunit selectively controls tLTD by modulating dendritic calcium transients evoked by backpropagating action potentials.